Energy Intensity and Ghg Production of Chosen Propulsions Used in Road Transport - Tomas Skrucany; Stefania Semanova; Tomasz Figlus; Branislav Sarkan; Jozef Gnap (Communications - Scientific letters of the University of Zilina, 2017)
Nowadays, there are more types of propulsions and fuels in road transport. This paper deals with the problem of their energy intensity and GHG emissions. The emissions can be classified as primary or secondary. The mixture of primary sources for the production of fuel or energy influence the final value of the ecological effectiveness of the propulsion. Methodology of the standard EN 16258:2012 was used for the estimation of this value.